Determination of Fintech and Fear of Missing Out on Digital Financial Management Behavior Through Digital Financial Literacy Among Generation Z in Jepara - Bethania Amanda Stevanie (Generate Digital Publishing, 2026)
Objective: This study aims to analyze the influence of financial technology (fintech) and fear of missing out (FOMO) on digital financial management, with digital financial literacy as a mediating variable, among Generation Z in Jepara Regency.Research Design & Methods: This study employs a quantitative approach using primary data collected via a questionnaire administered to 180 Generation Z respondents in Jepara. The sampling technique utilized non-probability sampling with a purposive method. Data analysis was performed using Partial Least Squares-based Structural Equation Modeling (SEM-PLS) via SmartPLS software, including tests of the measurement model (outer model) and the structural model (inner model), as well as a mediation testFindings: The results of the study indicate that digital financial literacy has a positive and significant effect on digital financial management. Financial technology also has a significant effect on both digital financial literacy and digital financial management. Conversely, FOMO has no significant effect on either variable. The mediation analysis shows that digital financial literacy does not mediate the relationship between FOMO and digital financial management. Still, it does significantly mediate the effect of fintech on digital financial management.Implications: These findings underscore the importance of improving digital financial literacy as a key factor in promoting effective financial management practices, and the need for regulators and fintech providers to strengthen technology-based financial education.Contribution & Value Added: This study provides empirical insights into the mediating role of digital financial literacy and enriches the literature on Generation Z’s financial behavior in the context of fintech in non-metropolitan areas.